EMERGING STRATEGIES FOR IMPROVING LITERACY SKILLS: A COMPREHENSIVE LITERATURE REVIEW - Loso Judijanto; Parni Parni (Indonesian Journal of Education (INJOE), 2025)
This research aims to identify and analyse the evolving strategies in improving literacy through a comprehensive literature review. The main focus of this study is to understand the role of educational innovations in addressing literacy challenges in various contexts. By reviewing various sources or references, it was found that the use of digital technologies, such as reading platforms and educational apps, plays an important role in increasing student participation and interest in reading. In addition, the active involvement of teachers, parents and communities proved essential in shaping an enabling environment for literacy reinforcement. Thus, an adaptive and technology-based approach to literacy, supported by effective collaboration among stakeholders, can significantly improve literacy outcomes.